Intermittent fasting and gut microbiota - Karakan, Tarkan (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Karakan T. Intermittent fasting and gut microbiota. Turk J Gastroenterol 2019; 30(12): 1008.